Exchange rate: fix, float, or manage it? - Bresser-Pereira, Luiz Carlos (2008)
The Exchange Rate is the Most Strategic of the Four Macroeconomic Prices. it Determines not Only Exports and Imports, But Also Real Wages, Consumption and the Savings Rate. Conventional Theory Holds That it is Impossible to Manage It, and That the Only Alternatives are to Fix or to Float It. the Experience of the East Asian Countries, That Use it Strategically, Demonstrates That This Claim is False.